2015
DOI: 10.1002/etc.2973
|View full text |Cite
|
Sign up to set email alerts
|

Species interactions and chemical stress: Combined effects of intraspecific and interspecific interactions and pyrene on Daphnia magna population dynamics

Abstract: Species interactions are often suggested as an important factor when assessing the effects of chemicals on higher levels of biological organization. Nevertheless, the contribution of intraspecific and interspecific interactions to chemical effects on populations is often overlooked. In the present study, Daphnia magna populations were initiated with different levels of intraspecific competition, interspecific competition, and predation and exposed to pyrene pulses. Generalized linear models were used to test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 37 publications
4
29
1
Order By: Relevance
“…Using the SSD method, a predicted noeffect concentration (PNEC, significance level 5%) of 0.076 mg L −1 was derived from the single-species toxicity test data collected in literature (Table 5) and those calculated in this study (Table 4), which was also lower than TCPE. The results from this experiment indicate that interspecies competition and grazing reduced the toxic effect of petroleum hydrocarbons at the community level, with similar studies on this topic also being reported (Arco et al, 2015;Viaene et al, 2015). Contrary to observations in the present study, species interactions have been found to result in greater toxic effects of pollutants (Foit et al, 2012;Gergs et al, 2013).…”
Section: Threshold Concentration Of Petroleum Hydrocarbonssupporting
confidence: 85%
See 1 more Smart Citation
“…Using the SSD method, a predicted noeffect concentration (PNEC, significance level 5%) of 0.076 mg L −1 was derived from the single-species toxicity test data collected in literature (Table 5) and those calculated in this study (Table 4), which was also lower than TCPE. The results from this experiment indicate that interspecies competition and grazing reduced the toxic effect of petroleum hydrocarbons at the community level, with similar studies on this topic also being reported (Arco et al, 2015;Viaene et al, 2015). Contrary to observations in the present study, species interactions have been found to result in greater toxic effects of pollutants (Foit et al, 2012;Gergs et al, 2013).…”
Section: Threshold Concentration Of Petroleum Hydrocarbonssupporting
confidence: 85%
“…Similarly, the decrease in zooplankton biomass might result from the increased zooplankton grazing rate and decreased survival rate. A reduction in the toxic effects of pyrene on Daphnia magna (a small, planktonic crustacean) when combined with predation and competition from rotifers has been observed previously (Viaene et al, 2015), which was attributed to differences in the population structure of D. magna and inhibition in the feeding rate of predators. The combination of rotifer competition and exposure to the fungicide carbendazim led to increasing abundances of D. magna at all life stages in comparison with the competition controls and was related to the superior grazing capacity of D. magna versus rotifers and the uptake of rotifers by D. magna in food limiting conditions (Arco et al, 2015).…”
Section: Toxic Effects Endpointsmentioning
confidence: 56%
“…When under interspecific competition (by “ D. longispina + small rotifers”) the B. calyciflorus abundance declined faster than when not under interspecific competition and even went extinct in some jars (Figure A and B). Cladocerans compete with rotifers for food and are generally known to outcompete (they have a faster filtration rate, can ingest a wider range of algae cells, and have a bigger energy reserve) and suppress rotifer populations (Gilbert ; MacIsaac and Gilbert ; Del Arco et al ; Viaene et al ). In addition, cladocerans can damage the rotifers themselves (by being swept into the branchial chamber of the Cladocera: mechanical interference), and this can have a negative effect on the rotifer populations (MacIsaac and Gilbert ).…”
Section: Resultsmentioning
confidence: 99%
“…Under natural conditions, however, populations can experience a variety of abiotic (e.g., temperature, nutrients) and biotic (e.g., competition, predation) factors that could interact with toxicant exposure effects (Laskowski et al ; Moe et al ). The competition for resources between (interspecific) and within (intraspecific) species is one of the major biotic interactions and can significantly modify the responses of organisms to toxicants (De Laender et al ; Stampfli et al ; Gergs et al ; Del Arco et al ; Viaene et al ). For example, a decrease of the most sensitive species attributable to the toxic effects of a toxicant (direct effect) can lead to an increase of a more resistant species (indirect effect) as a result of decreased competition or to a decrease of the consumer species as a result of starvation (Fleeger et al ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the no-observed-effect concentration of the herbicide prometryn to ciliates was found to be approximately 145 times lower in a bitrophic microcosm compared with single-species tests. Intraspecific competition can also change the sensitivity to pesticides (Foit et al 2012a;Viaene et al 2015), and indirectly altered predation rates can lead to cascading effects on other trophic interactions and ecosystem functions (Englert et al 2012;Agatz et al 2014;Viaene et al 2015). Intraspecific competition can also change the sensitivity to pesticides (Foit et al 2012a;Viaene et al 2015), and indirectly altered predation rates can lead to cascading effects on other trophic interactions and ecosystem functions (Englert et al 2012;Agatz et al 2014;Viaene et al 2015).…”
Section: Introductionmentioning
confidence: 99%